IMPLEMENTASI PELAPORAN KEUANGAN BERBASIS AKRUAL PADA RUMAH SAKIT UMUM DAERAH (Studi Kasus pada RSUD Tugurejo Tahun 2018) - Nurulita Irmaya Adelina; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2019)
This study aims to describe how the implementation of accrual based in the financial report of hositals. This study focused on the Rumah Sakit Umum Daerah (RSUD) Badan Layanan Umum Daerah (BLUD). BLUSs are formed to provide services to the community without seeking profits based on the principles of efficiency and productivity. BLUDs carried out accounting and financial statements using an accrual basis. The location of this study is RSUD Tugurejo. This study used qualitative descriptive approach with interview and observation methods of employees in the accounting sub section RSUD Tugurejo as parties directly involved in hospital financial reporting. Data from interviews and observation was analyzed by using Miles and Huberman model and categorized as major determinants on implementing accrual based RSUD financial report. The result showed that determinants which affected on implementing accrual basedin financial reports were accounting and information technology based system, commitment from leader, competent human resources, and resistance to change. The four determinants related each other. The manual accounting system was chosen when a computerized and integrated accounting system was not ready to be used which required competent human resources to use it. Commitment from leaders who supports the application of accrual basis accounting were needed to realize the acceptance of accrual basis accounting.